A identidade e a expressão de gênero do paciente podem influenciar a decisão de tratamento do cirurgião dentista? - Cassol, Tássia (2024)
Unlike sex, which is determined at birth, the term gender has social and cultural connotations. Gender identity is an individual's self-perception that may or may not be congruent with the biological sex. Gender expression is how a person manifests his own identity publicly. From the point of view of intersectionality, social factors are all connected and are responsible for defining the identity of individuals or groups. Thus, studying gender issues implies elucidating different meanings and social contexts. The aim of the study is to verify whether the patient's gender identity and expression can influence the dentist's decision-making. This is a randomized study in which dentists from a city in southern Brazil were divided into two groups by drawing lots and invited to complete self-administered questionnaires containing a hypothetical clinical case. The only difference between the clinical cases was the patient's gender identity. One referred to a transgender woman (case A) and the other to a cisgender woman (case B). The outcome of the study was the treatment decision for each scenario (anterior and posterior tooth), presented according to the patient's gender identity. Poisson Regression models with robust variance estimated crude and adjusted prevalence ratios with their respective 95% confidence intervals. Participated in the study 204 dentists. Conservative treatment decisions predominated for both clinical cases, however, the covariates associated with the outcomes were different. For the trans woman, younger professionals (PR=2.32; 95%CI 1.12-4.82) and those who had a specific field in the medical record for the chosen name (PR=2.38; 95%CI 1.001-5.65/ PR=1.93; 95%CI 1.04-3.55) decided for more invasive treatments, while those who graduated from public universities (PR=0.40; 95%CI 0.17-0.90) decided for more conservative treatments. For the cis woman, female professionals (PR=0.34; 95%CI 0.17-0.68), without formal employment ties (PR=0.58; 95%CI 0.34-0.98) and with one specialization course (PR=0.27; 95%CI 0.12-0.60) decided for more conservative treatments, while those who accepted dental insurance (PR=2.16; 95%CI 1.21-3.86) and received training on transgender health (PR=2.10; 95%CI 1.24-3.55/ PR=1.91; 95%CI 1.24-3.55) decided for more invasive treatments. The factors associated with treatment decision were different for the trans and cis woman patient. However, gender identity did not seem to influence the professionals' decision-making.